2018
DOI: 10.1007/jhep05(2018)174
|View full text |Cite
|
Sign up to set email alerts
|

Skyrmions in models with pions and rho mesons

Abstract: A problem with the standard Skyrme model is that Skyrmion binding energies are around 15%, being much larger than the order 1% binding energies of the nuclei that they aim to describe. Here we consider theories that extend the standard Skyrme model of pions by including rho mesons, via dimensional deconstruction of Yang-Mills theory with an extra dimension. We report the first results of parallel numerical computations of multiSkyrmions in theories of this type, including a model that reduces Skyrmion energies… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 41 publications
0
26
0
Order By: Relevance
“…A modified model with low classical binding energies (such as those developed in Refs. [10][11][12][13][14][15][16][17]) will also have lower vibrational frequencies and hence more realistic quantum states. In addition, and especially in the lightly bound models, the potential energy may be significantly anharmonic-a difficult feature to account for.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A modified model with low classical binding energies (such as those developed in Refs. [10][11][12][13][14][15][16][17]) will also have lower vibrational frequencies and hence more realistic quantum states. In addition, and especially in the lightly bound models, the potential energy may be significantly anharmonic-a difficult feature to account for.…”
Section: Resultsmentioning
confidence: 99%
“…where m is the dimensionless pion mass which we fix as m ¼ 1. One may modify the Lagrangian in a number of ways [10][11][12][13][14][15][16][17]. For static, finite energy configurations the potential term ensures that Φ ¼ ð1; 0; 0; 0Þ at spatial infinity.…”
Section: Problem and Methodsmentioning
confidence: 99%
“…One is to include vector mesons in the Lagrangian. Recently it was shown that inclusion of the rho meson reduces the classical binding energy by two-thirds, while retaining the symmetry group of each Skyrmion up to baryon number eight [22]. If one integrates out the mesons, a term which contains sixth order derivatives of the pion field appears [23].…”
Section: (55)mentioning
confidence: 99%
“…Hence, if such a bound could be saturated, then classically the binding energy would vanish exactly. In the last decade, this approach has been taken in three different directions: the vector meson Skyrme model [12][13][14], the BPS-Skyrme model [15,16] and the lightly/loosely bound Skyrme models [17][18][19].…”
Section: Introductionmentioning
confidence: 99%